Association Between Low Colonic Short-Chain Fatty Acids and High Bile Acids in High Colon Cancer Risk Populations - Ou, Junhai (Nutr Cancer, 2011)
We propose that the influence of diet on colon cancer risk is mediated by the microbiota. To investigate how dietary fat influences risk, we compared the colonic contents of 12 adult high-risk African Americans (AAs) and 10 Caucasian Americans (CAs) who consumed a high-fat diet (123 ± 11 g/d and 129 17 g/d, respectively) to 13 native Africans (NAs) who subsisted on± a low-fat (383.0 g/d) diet, all aged 50–60 yr. The colonic bile acids were measured±by LC-MS and the short-chain fatty acids (SCFAs) by GC. The chief secondary colonic bile acids, deoxycholic acid and lithocholic acid, were correlated with fat intake and similar between AAs and CAs, but 3–4 times higher than in AAs (p < 0.05). The major SCFAs were lower in AAs (p < 0.001) and CAs (p < 0.001) compared to AAs, but conversely, the branched chain fatty acids (BFCA) were higher. Our results suggest that the higher risk of colon cancer in Americans may be partly explained by their high-fat and high-protein, low complex carbohydrate diet, which produces colonic residues that promote microbes to produce potentially carcinogenic secondary bile acids and less antineoplastic SCFAs. The role of BCFA in colonic carcinogenesis deserves further study.